FORMING CHILDREN'S SPIRITUAL-MORAL IMMUNITY AGAINST MORAL ATTACKS IN THE EDUCATIONAL PROCESS (Universal International Scientific Journal, 2026)
This article discusses the influence of the environment, educators, and parents in forming children's moral and ethical immunity against moral attacks during the educational process, and the environment created in the educational and upbringing process to cultivate strong moral and ethical views that can protect children from various harmful ideas, harmful habits, and negative influences in the environment.
Keywords: spiritual - moral immunity, moral attacks, child upbringing, educational process, spiritual education, moral values, pedagogical influence, educational environment, national and universal values, family and school cooperation, critical thinking and youth spirituality